PENGARUH ATRIBUT WISATA TERHADAP KEPUASAN WISATAWAN PANTAI JINGGA DI MUARA BADAK - HERLISA, HERLISA; FAHLETI, WIDYA HANA (SEKOLAH TINGGI ILMU EKONOMI TENGGARONG, 2021)
This study aims to determine the effect of the attractions, facilities and accessibility variables simultaneously and partially on the satisfaction of Jingga Beach tourists in Muara Badak. Sampling was done by means of puprosive sampling, namely by distributing questionnaires to tourists who had been to Jingga Beach in Muara Badak for two weeks as many as 60 respondents. Then analyzed using multiple linear regression analysis method. The results obtained show that attractions have an effect on tourist satisfaction, while facilities and accessibility have no effect. Attractions, facilities and accessibility simultaneously influence Jingga Beach tourists in Muara Badak.Â